Phosphonium-containing diblock copolymers from living anionic polymerization of 4-diphenylphosphino styrene. Issue 5 (20th November 2015) - Schultz, Alison R.; Fahs, Gregory B.; Jangu, Chainika; Chen, Mingtao; Moore, Robert B.; Long, Timothy E.
Abstract : Living anionic polymerization of 4-diphenylphosphino styrene (DPPS) achieved well-defined homopolymers, poly(DPPS- b -S) styrenic block copolymers, and poly(I- b -DPPS) diene-based diblock copolymers with predictable molecular weights and narrow polydispersities. Abstract : Living anionic polymerization of 4-diphenylphosphino styrene (DPPS) achieved well-defined homopolymers, poly(DPPS- b -S) styrenic block copolymers, and poly(I- b -DPPS) diene-based diblock copolymers with predictable molecular weights and narrow polydispersities. In situ FTIR spectroscopy monitored the anionic polymerization of DPPS and tracked monomer consumption for kinetic analysis. Post-alkylation enabled controlled placement of phosphonium functionality in poly(I- b -DPPS) diblock copolymers, producing well-defined phosphonium-containing block copolymers with low degrees of compositional heterogeneity. Incorporating phosphonium charge disrupted the lamellar bulk morphology of the neutral diblock precursor and provided morphologies with interdigitated packing of alkyl chains on the phosphonium cation.